Iron Ore Beneficiation through Reverse Flotation: Advances in Nanobubble-Assisted Flotation Technology for Lean Grade Ore Upgradation and Silica Removal: A Review - Mihir D.M.; Attel Umasanka (International Journal of Minerals, 2026)
The global demand for high-grade iron ore concentrates continues to surge as readily available rich ores become depleted. Iron ore beneficiation through froth flotation has emerged as a critical technology for upgrading lean-grade iron ores (typically 25–35% Fe) to produce high-quality concentrates (64–70% Fe) suitable for direct reduction and blast furnace operations. This comprehensive review examines the fundamental principles of flotation in iron ore beneficiation, with particular emphasis on the revolutionary impact of nanobubble (NB) assisted flotation technology. Nanobubbles, ultrafine bubbles with diameters ranging from 300 to 700 nm, offer unprecedented advantages in enhancing flotation kinetics, collector adsorption efficiency, and mineral selectivity for the separation of fine and ultrafine particles. This paper synthesizes the current state of the art in nanobubble generation via hydrodynamic cavitation, the mechanisms of nanobubble-enhanced flotation, surface chemistry fundamentals, and the critical role of reverse flotation (cationic and anionic) in silica removal from lean iron ores. Industrial case studies from global operations, process intensification strategies, and comparative analyses of nanobubble versus conventional flotation demonstrate improvements in iron recovery (20 to 40 percentage points), flotation rate acceleration (30 to 50%), and a significant reduction in reagent consumption. The paper addresses current challenges in processing Anshan-type ores and other refractory hematite deposits, discusses scale-up considerations, and projects future research directions in nanobubble-assisted flotation for sustainable iron ore beneficiation.
Keywords: Iron ore; Mineral processing; collector adsorption; flotation; hydrodynamic cavitation; lean grade ores; nanobubbles; reverse flotation; silica removal; surface chemistry